1999
DOI: 10.1002/jor.1100170619
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance‐1 and p‐glycoprotein in human chondrosarcoma cell lines: Expression correlates with decreased intracellular doxorubicin and in vitro chemoresistance

Abstract: We report on two chondrosarcoma cell lines, FS and AQ, that may be used as models of multidrug resistance in chondrosarcoma. Multidrug resistance-1 expression was assayed with reverse transcription-polymerase chain reaction. Immunostaining for the multidrug resistance-1 product, P-glycoprotein, was performed with the monoclonal antibody C494. Intracellular levels of doxorubicin were measured by fluorescent emission at 590 nm after 1 hour of incubation with the agent and again after 1, 2, and 4-hour washout per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Moreover, some studies indicate that chondrosarcoma cells can express multidrug-resistance gene products, such as P-glycoprotein, thereby reducing the absorption of drugs, and giving rise to chemotherapy resistance [18, 19]. Surgical resection remains the primary mode of treatment for chondrosarcomas.…”
Section: Chondrosarcomasmentioning
confidence: 99%
“…Moreover, some studies indicate that chondrosarcoma cells can express multidrug-resistance gene products, such as P-glycoprotein, thereby reducing the absorption of drugs, and giving rise to chemotherapy resistance [18, 19]. Surgical resection remains the primary mode of treatment for chondrosarcomas.…”
Section: Chondrosarcomasmentioning
confidence: 99%
“…In addition to prolonged doubling time and limited vascularity it has been suggested that the multidrug-resistance 1 gene (MDR-1) P-glycoprotein may play a role in chemotherapy resistance. 49,50 For conventional chondrosarcoma, current recommendations do not include use of adjuvant or neo-adjuvant chemotherapy.…”
Section: Chondrosarcomamentioning
confidence: 99%
“…An explanation for chemotherapy resistance may be the expression of the multidrug-resistance 1 gene P-glycoprotein, resulting in resistance to doxorubicin in vitro [97]. The effect of chemotherapy on grade II and III chondrosarcomas is difficult to assess because the number of reported cases is very low and the reported series are mostly retrospective.…”
Section: Chondrosarcomamentioning
confidence: 99%